Promoting Optimal Physical Exercise for Life (PROPEL): aerobic exercise and self-management early after stroke to increase daily physical activity—study protocol for a stepped-wedge randomised trial. Issue 6 (30th June 2017) - Mansfield, Avril; Brooks, Dina; Tang, Ada; Taylor, Denise; Inness, Elizabeth L; Kiss, Alex; Middleton, Laura; Biasin, Louis; Fleck, Rebecca; French, Esmé; LeBlanc, Kathryn; Aqui, Anthony; et al.
Abstract : Introduction: Physical exercise after stroke is essential for improving recovery and general health, and reducing future stroke risk. However, people with stroke are not sufficiently active on return to the community after rehabilitation. We developed the Promoting Optimal Physical Exercise for Life (PROPEL) programme, which combines exercise with self-management strategies within rehabilitation to promote ongoing physical activity in the community after rehabilitation. This study aims to evaluate the effect of PROPEL on long-term participation in exercise after discharge from stroke rehabilitation. We hypothesise that individuals who complete PROPEL will be more likely to meet recommended frequency, duration and intensity of exercise compared with individuals who do not complete the programme up to 6 months post discharge from stroke rehabilitation. Methods and analysis: Individuals undergoing outpatient stroke rehabilitation at one of six hospitals will be recruited (target n=192 total). A stepped-wedge design will be employed; that is, the PROPEL intervention (group exercise plus self-management) will be 'rolled out' to each site at a random time within the study period. Prior to roll-out of the PROPEL intervention, sites will complete the control intervention (group aerobic exercise only). Participation in physical activity for 6 months post discharge will be measured via activity and heart rate monitors, and standardised physical activity questionnaire. Adherence to exercise guidelines will be evaluated by (1) number of 'active minutes' per week (from the activity monitor), (2) amount of time per week when heart rate is within a target range (ie, 55%–80% of age-predicted maximum) and (3) amount of time per week completing 'moderate' or 'strenuous' physical activities (from the questionnaire). We will compare the proportion of active and inactive individuals at 6 months post intervention using mixed-model logistic regression, with fixed effects of time and phase and random effect of cluster (site). Ethics and dissemination: To date, research ethics approval has been received from five of the six sites, with conditional approval granted by the sixth site. Results will be disseminated directly to study participants at the end of the trial, and to other stake holders via publication in a peer-reviewed journal. Trial registration number: NCT02951338; Pre-results.